What Happens When a Country Does Not Adjust to Terms of Trade Shocks? The Case of Oil-Rich Gabon - Zafar, Ali (World Bank, Washington, D.C., 2013)
Gabon is currently one of the richest countries in Sub-Saharan Africa, having a GDP per capita of close to $4,000, and is characterized by a stable political climate and rich forestry and mineral resources, as well as a small population. Oil is the key economic sector, accounting for half of GDP and more than two-thirds of revenue. Discovered in the 1970s, oil windfalls have delivered spectacular wealth and financed public expenditure over two decades. However, the oil boom has led to the Dutch disease and the shrinkage of the industrial and agricultural sectors of the economy due to the appreciation of the exchange rate and the movement of capital to the oil sector. But with output projections suggesting that oil will be depleted within the next 10 to 15 years, there are growing pressures on the policymakers to take actions to diversify production. While Gabon's membership in the Central African economic and monetary union means that it benefits from the macroeconomic stability from a common external trade and fixed exchange rate regime pegged to the euro, it relinquishes independence in the policy response to shocks. An analysis using a quantitative methodology to decompose responses to shocks shows that Gabon's adjustment to adverse movements in the terms and trade from 1980 to 2000 was considerably weak in terms of three performance indicators-import intensity, economic compression, and nonoil export promotion. While the economy's growth rate was respectable, policymakers postponed adjustment by resorting to considerable borrowing during this period. While there was some decrease in import intensity from 1987 to 1990 and 1996 to 2000, as well as slight non-oil export diversification from 1996 to 2000, the government borrowed from commercial banks and donors, causing its external debt/GDP ratio to increase from 30 percent of GDP in 1970-76 to 80 percent in 1999. To pay the debt service, it currently has to maintain large primary surpluses. Only since 1996 has there been significant fiscal retrenchment and a freezing of government wages.